A heuristic for the minimization of open stacks problem - Ashikaga,Fernando Masanori (2009)
It is suggested here a fast and easy to implement heuristic for the minimization of open stacks problem (MOSP). The problem is modeled as a traversing problem in a graph (Gmosp) with a special structure (Yanasse, 1997b). It was observed in Ashikaga (2001) that, in the mean experimental case, Gmosp has large cliques and high edge density. This information was used to implement a heuristic based on the extension-rotation algorithm of Pósa (1976) for approximation of Hamiltonian Circuits. Additionally, an initial path for Pósa's algorithm is derived from the vertices of an ideally maximum clique in order to accelerate the process. Extensive computational tests show that the resulting simple approach dominates in time and mean error the fast actually know Yuen (1991 and 1995) heuristic to the problem.